INFLUENCE ECOMMERCE ON TOKOPEDIA BRAND PERFORMANCE: THE ROLE OF BRAND AWARENESS DIFFERENTIATION ADVANTAGES - Merry M. Pelupessy; Etvin Rizal Tamher; Vanessa Bakarbessy (SEAN Institute, 2023)
This research discusses how E-commerce affects brand performance on Tokopedia with brand awareness differentiation as a mediating variable. The purpose of this research is to test and analyze the influence of brand awareness differentiation mediating brand ambassadors and the Korean wave on Tokopedia brand performance. The large research population meant that the sample was narrowed down using Hair calculations which made the research sample total 80 people, with the sampling technique used being non-probability sampling technique and the method used was purposive sampling. The analysis test tool used is SmartPLS 3.0 with the SEM (Structural Equation Modeling) analysis method. The results of this research show that brand ambassadors have a negative but not significant effect on brand awareness differentiation, Korean wave has a negative but significant effect on brand awareness differentiation, and brand awareness differentiation has a positive but not significant effect on brand performance.